Pengaruh Motivasi Investasi dan Pengetahuan Investasi terhadap Minat Investasi di Pasar Modal pada Mahasiswa Politeknik Negeri Medan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the influence of investment motivation and financial knowledge on college students’ interest in capital market investment. The study applies a quantitative research design using a structured questionnaire distributed to 300 students of Politeknik Negeri Medan, with participants chosen through cluster random sampling to ensure representation across academic groups. Data analysis was conducted through multiple linear regression using IBM SPSS version 29, preceded by validity, reliability, and classical assumption tests to guarantee the accuracy and reliability of the findings. The results indicate that both investment motivation and financial knowledge have a significant and positive effect on students’ enthusiasm for participating in capital market activities. This suggests that students who possess higher motivation and better comprehension of capital market instruments, particularly stocks, demonstrate greater involvement in investment practices. Consequently, enhancing students’ exposure to investment education and building awareness of market opportunities can play an important role in encouraging broader participation among young potential investors.